Morphology and evolution of the wing bullae in South American Leptophlebiidae (Ephemeroptera) - Dominguez, Eduardo (2018)
Insects were the first animals to take to the skies, and have been flying for over 320 million years. The order Ephemeroptera is, or at least is part of, the most early-diverging lineage of extant winged insects. The extant species present a very short adult life span, mainly dedicated to reproduction and dispersal of eggs. Mating and egg-laying behavior depend on flight. Wings are structures to fly and as such face a number of physical and physiological challenges. The convex curvature along the anterior–posterior axis of the wing generates a camber that must be carefully regulated. One of the most interesting ways of wing bending is provided by the bullae, which have been defined as short sections of flexible chitin, where the flexion lines cross veins. Although the bullae have been frequently used as taxonomic characters, there is no study focused on their morphology, although their prevalence on the wings of mayflies strongly suggests a role in flight. In order to identify evolutionary trends of these structures within Ephemeroptera, we constructed a matrix with comparative anatomy data of the bullae from whole mounts of the wings of 300 specimens belonging to 70 species of several mayfly families, as well as scanning microscopy samples of selected specimens. We also surveyed the number of bullae and their distribution in the wings of the different species within the South American Leptophlebiidae clade. We optimized the characters onto the latest published phylogeny for Leptophlebiidae.